Enhancing digital literacy and creativity makerspaces in the early years - Blum-Ross, Alicia 1979-; Kumpulainen, Kristiina 1966-; Marsh, Jackie (Routledge, 2020)
"One of the most exciting recent interventions that foster children's digital literacy and creative skills has been the advent of 'makerspaces'. This book shares insights from a project examining how young children develop creative skills and digital literacy through 'making.' Using case studies from environments like schools and museums, contributors show how children use hands-on experimentation as they make all kinds of texts and artefacts, using both traditional materials and new ones such as 3D printers. Editors argue that 'making', with its emphasis on play, experimentation and storytelling is uniquely positioned to explore the competencies of young children"--